Pengaruh Citra Merek, Persepsi Kualitas, dan Social Media Influencer Terhadap Loyalitas Merek Somethinc: Studi Pada Pengguna Produk Merek Somethinc: The Influence of Brand Image, Perceived Quality, and Social Media Influencer On Brand Loyalty of Somethinc: A Study of Somethinc Beauty Brand - Ujang Sumarwan; Popong Nurhayati; Fairuz Malinda Rahma (School of Business, Bogor Agricultural University (SB-IPB), 2023)
Somethinc is a new beauty brand that has a great demand by consumers. Many researchers are interested to researched on Somethinc with different research focuses. This study aims to analyze the effect of perceived quality, social media influencers, and the role of mediating brand image on Something's brand loyalty and to analyze the factors that influence brand loyalty by consumers to Something's products. This study used SEM-PLS analysis on 222 respondents aged 15-64 years and had bought and used Somethinc products. The results showed that perceived quality (PQ) had a positive and significant effect on brand image (BI) and brand loyalty (BL). Brand image (BI) also has a positive influence on brand loyalty (BL). Brand image (BI) can also be a mediator between perceived quality (PQ) and brand loyalty (BL). In this study, brand image (BI) is not a mediator between social media influencers (SMI) and brand loyalty (BL). In this study, social media influencers (SMI) have a negative and non-significant relationship to brand image (BI) and brand loyalty (BL). Therefore, to increase Something's brand loyalty (BL), Somethinc can improve perceived quality (PQ) and brand image (BI). Perceived quality can be increased by develop the product, made some product innovations that fit consumer needs, and provide a great service for consumers. Brand image of Somethinc can be increased by optimizing the use of social media and consistently make content that can strengthen a good brand image. Keywords: brand image, brand loyalty, perceived quality, social media influencer, somethinc